Financial Outreach and Working Poverty in Developing Countries : New Evidence from Bank Penetration - Coulibaly, Aissata; Yogo, Urbain Thierry (World Bank, Washington, DC, 2018)
Although a growing body of literature emphasizes that the poor may benefit from better access to financial services through more growth and employment opportunities, there is a continuing debate about the mechanism and extent to which such access would reduce inequalities. Considering that labor is the main asset of the poor, this paper investigates the impact of access to financial services, measured by the number of bank branches, on working poverty and inequality in the labor market. The study uses a panel of 63 developing countries over 2004-13 to demonstrate that improving financial access reduces the proportion of poor workers, especially in countries hit by macroeconomic instability. The analysis shows that the negative impact on working poverty is two times less important than the positive impact on workers at the top of the income distribution, suggesting an increase in inequality. But this effect is mitigated, since the study finds evidence that providing greater access to financial services for relatively rich workers can have a strong effect on decreasing working poverty.